Determinants of Bacille Calmette-Guérin scarification in Danish children - Trine Mølbæk Jensen; Signe Kjeldgaard Jensen; Nina Marie Birk; Andreas Rieckmann; Thomas Hoffmann; Christine Stabell Benn; Dorthe Lisbeth Jeppesen; Ole Pryds; Thomas Nørrelykke Nissen (Heliyon, 2021)
Background: Studies in low-income countries have shown that among Bacille Calmette-Guérin (BCG) vaccinated children, those who develop a BCG-scar have significantly better survival than those who do not develop a scar. In a Danish multicenter randomized clinical trial we assessed determinants for developing a BCG-scar and for BCG scar size following neonatal BCG vaccination. Methods: At three Danish hospitals, newborns were randomized 1:1 to BCG vaccination or no BCG vaccination. The infants were invited for a clinical examination at the ages of 3 and 13 months. At 13 months, the scar site was inspected and scar size measured. We investigated three groups of determinants; external, parental, and individual-level determinants on relative scar prevalence and differences in median scar sizes. Results: Among 2118 BCG vaccinated infants, 2039 (96 %) were examined at 13 months; 1857 of these (91 %) had developed a BCG-scar. Compared with Copenhagen University Hospital, Hvidovre (85 %), Copenhagen University Hospital, Rigshospitalet had a scar prevalence of 95 % (adjusted Prevalence ratio (aPR) = 1.24 [CI 95 %: 1.18 to 1.30]); it was 93 % at Kolding Hospital (aPR 1.27 [CI 95 %: 1.19 to 1.35]). Increasing vaccine experience was positively associated with developing a scar and with scar size. Conclusion: Across multiple potential determinants of BCG scaring and size, logistical factors dominated. The results support that injection technique is an important determinant of developing a scar. Given the strong link between having a BCG scar and subsequent health, improved BCG vaccination technique could play a major role for child health.